The Influence of Human Resource Management on Teacher Work Motivation - Limega Candrasa; Willy Cahyadi; Lukieto Cahyadi; Cia Cai Cen (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Effective human resource management contributes significantly to enhancing teachers’ motivation and improving the quality of learning. This study aims to examine the impact of Human Resource Management (HRM) work on the motivation of junior high school teachers. Using a descriptive qualitative approach, this study focuses on an in-depth understanding of HRM practices in schools and teachers' perceptions of their influence on work motivation. Data were collected through in-depth interviews with principals and teachers, direct observation in the school environment, and documentation studies related to HRM policies and practices. Data analysis was carried out using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that the implementation of HRM including recruitment, training, performance evaluation, and rewarding in general has a positive contribution to teacher work motivation, especially in terms of teaching enthusiasm, loyalty, and sense of responsibility. However, several obstacles were also found such as limited ongoing training and the lack of a fair reward system. This study recommends the need to strengthen HRM strategies based on teacher needs in order to improve the quality and work enthusiasm sustainably.